2021
DOI: 10.2147/jmdh.s329344
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Health-Promoting Behaviors of Hospitalized Patients with Non-Communicable Diseases During the Second Wave of COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has affected the health-related behaviors of patients with non-communicable diseases (NCDs). Thus, the factors predicting the health-promoting behaviors (HPBs) of hospitalized patients with NCDs during the second wave of COVID-19 should be examined. Objective The aims of this study were to determine the relationships among the patients’ characteristics, perceived self-efficacy, social support, perception of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Most of the new cases spread rapidly through diverse communities. [1][2][3][4] Worldometer 5 reported that as of October 3, 2021, the total prevalence of global cases is 235 million and there have been 4.81 million deaths. As mentioned earlier, the healthcare providers, who are working as the frontliners during the pandemic, are perceived to be overwhelmed and experiencing burnout, even posttraumatic stress disorder (PTSD), from the deluge of COVID-19 cases they have been handling.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the new cases spread rapidly through diverse communities. [1][2][3][4] Worldometer 5 reported that as of October 3, 2021, the total prevalence of global cases is 235 million and there have been 4.81 million deaths. As mentioned earlier, the healthcare providers, who are working as the frontliners during the pandemic, are perceived to be overwhelmed and experiencing burnout, even posttraumatic stress disorder (PTSD), from the deluge of COVID-19 cases they have been handling.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Making decisions about how to follow health advice was one of the processes necessary for COVID-19 prevention behaviors. 12 Health literacy (HL) is a concept addressed in healthcare systems and research on health promotion. 13 It constitutes the process by which individuals acquire knowledge and motivation and how they understand and access information, express opinions, and make decisions about promoting and maintaining health.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 ) Making decisions about how to follow health advice was one of the processes necessary for COVID-19 prevention behaviors. 12 )…”
Section: Introductionmentioning
confidence: 99%
“… 1 ) In Thailand, the prevalence of diabetes increased from 7.7% in 2004 to 7.8% in 2009 and 9.9% in 2014, 2 ) making it the second-ranking non-communicable disease, following high blood sugar levels. 3 , 4 ) Patients with long-term diabetes and inadequate blood glucose management are prone to develop complications that result in mortality and increased disease severity, 5 , 6 ) as well as acute respiratory distress syndrome in coronavirus disease 2019 (COVID-19), 7 ) mainly due to a higher incidence of diabetes-specific complications (e.g., coronary heart disease, stroke, kidney failure, and peripheral vascular disease). 8 ) Diabetic treatment aims to maintain blood sugar levels as close to standard as feasible.…”
Section: Introductionmentioning
confidence: 99%
“…1) In Thailand, the prevalence of diabetes increased from 7.7% in 2004 to 7.8% in 2009 and 9.9% in 2014, 2) making it the second-ranking non-communicable disease, following high blood sugar levels. 3,4) Patients with long-term diabetes and inadequate blood glucose management are prone to develop complications that result in mortality and increased disease severity, 5,6) as well as…”
mentioning
confidence: 99%